Pengalaman klien systemic lupus erythematosus dalam melakukan yoga di kota semarang - Hartati, Elis (Jurnal Keperawatan Soedirman, 2012)
Systemic lupus erythematosus (SLE) is a disease that can lead to disruption of all organs of the body. The one of preventive effort to reduce complaints in SLE is yoga. The aim of this research is to identify the client's experience of SLE in doing Yoga. Qualitative research method with phenomenology approach was used in this study. Study participants are 4 peoples. Data was analyzed by Colaizzi. The results revealed that the perceived benefits of yoga consists of three themes, namely physiological, psychological, and social. Physiological do not feel the complaint include lupus; relaxed; sleep needs are met; physically fresh; fever is reduced, more cheerful; improve laboratory results; reduces stiff; agency cape not; recover energy; lowering blood pressure. Psychological form of peace; obtain positive energy; friends with lupus; eliminating prejudice; closer to God. Social benefits that learning about life; improve interactions with others. Nurses are expected to increase the knowledge and benefits of yoga, to help establish social support on the client SLEÃ‚Â